Phenotypes associated with MAPT duplications: Genetics/genetic factors of non‐Alzheimer's tauopathies. (7th December 2020) - Wallon, David; Bonnevalle, Antoine; Rovelet‐Lecrux, Anne; Lagarde, Julien; Sarazin, Marie; Bottlaender, Michel; Sellal, François; Jonveaux, Therese; Heitz, Camille; Magnin, Eloi; Ber, Isabelle Le; Epelbaum, Stéphane; et al.
Abstract: Background: Duplication of the 17q21.3 region, leading to increased MAPT expression, causes a rare atypical early‐onset dementia (EOD) mimicking Alzheimer's Disease (AD) clinical presentation. Since our initial report in 2016, the same duplication has been identified in additional patients including 2 progressive supranuclear palsy (PSP) patients. It remains unclear whether MAPT duplication‐associated phenotypes are purely cognitive and if clinical and neuroimaging data are suggestive of a pure tauopathy or an amyloid plus tau underlying pathology. Method: We report in this study clinical and paraclinical data from 10 MAPT duplication carriers, including 8 with a clinical EOD presentation and two recently identified during the screening of a series of PSP cases. All clinical data were collected as well as family history, neuropsychological assessment, 3D‐structural MRI (n = 7 patients), fluorodesoxyglucose‐PET (n = 5), DaTSCAN SPECT (n = 2), Amyloid‐PET (n = 3) and Tau‐PET (n = 2). Six patients had AD cerebrospinal fluid (CSF) biomarkers measured. Results were interpreted following Amyloid/Tau/Neurodegeneration (A/T/N) classification. Result: Among the 10 patients, 6 had a positive family history of EOD, with cosegregation in one family. In one of the 4 sporadic patients, we could demonstrate that the duplication occurred de novo . Mean age of onset was 50.4 years [37‐58]. Eight presented a pure cognitive decline with an initial episodic amnesic syndrome. A behavioral dysexecutive syndrome was found in 5 patients (50%). Two patients were diagnosed as PSP but no or minor extrapyramidal signs were found among the 8 cognitive patients, despite 2 DaTSCANS showing presynaptic dopaminergic denervation. MRI of 6 cases (86%) showed hippocampal and temporoparietal bilateral atrophy. All CSF biomarkers were T+ and N+. Amyloid CSF biomarkers were abnormal in 3/6, suggestive of A+, however all three had negative amyloid‐PET. Interestingly, both Tau‐PET imaging showed strong deposits of Tau pathology within mesiotemporal regions and mild frontal cortex uptake in one patient (Figure). The neuropathology of two patients is currently being examined and will be presented. Conclusion: This largest series of MAPT duplications carriers shows a heterogeneous expression with clinical and neuroimaging data suggesting mixed cortical and subcortical impairment with diverse clinical consequences. We will confront these data to the results of the neuropathological examinations.